Caracterização estrutural e avaliação da capacidade imunomodulatória de exopolissacarídeos produzidos por lactobacilos isolados de Kefir - Igor Moura de Paiva (2013)
Kefir grains are characterized as an exopolysaccharide matrix, where a symbiotic community of bacteria and yeast are firmly embedded. The beverage is obtained by fermentation of the microorganisms, which compose the grains, in several possible types of growth medium, highlighting cow milk and aqueous solutions of sucrose. Exopolysaccharide can present one or more types of monosaccharide residues, so that homopolysaccharide synthesis involves only onegene while heteropolysaccharide synthesis involves several genes. These molecules present numerous biotechnology applications even in industry as in biomedical area. In this present work, it was performed identification of exopolysaccharide-producing lactobacilli strains, molecular characterization ofthe genes of the enzymes involved in the polymerization of glycidic residues, as wellas structural characterization and evaluation of immunomodulatory capacity of these biopolymers. Among 53 isolated lactobacilli strains from kefir grains which were utilized, 16 were considered exopolysaccharide-producing strains when cultivatedin MRS medium containing sucrose. Nucleotide sequences of the glucosyltransferases from L. kefiranofaciens 1P3, L. satsumensis10P and 10P2 and L. parafarraginis12P presented high indentity among them and identity of 74-75% with a sequence from the GenBank regarding to same enzyme of a L. hilgardii strain which also were isolated from kefir grains. The five exopolysaccharides which were characterized structurally presented only glucose in their polymeric chain and bound (1,6) e (1,4) in the proportions 92 and 8% respectively, being identified as dextrans (1P3, 10P, 10P2, 12P e 19U) and their molecular weight were greater than 500 KDa. T o evaluate the immunomodulatory capacity of the exopolysaccharides, mice treated with dextrans 1P3, 10P and 10P2 were compared with mice treated with saline. Their immunomodulatory effects under small intestine of the animals were evaluated by IgA production and by expression of the cytokines IL-5,IL-6, IL-10, IL-12p40, IL-17, IFN-, TGF-and TNF-. All dextrans stimulated an increase significant in the production of IgA. Animals which received dextran 1P3 presented reduced production of IL-10 and TGF-, whereas those which received dextran 10P2 had theexpression of TNF- increased.